2018
DOI: 10.1111/jcmm.13691
|View full text |Cite
|
Sign up to set email alerts
|

The family of 14‐3‐3 proteins and specifically 14‐3‐3σ are up‐regulated during the development of renal pathologies

Abstract: Chronic kidney disease, the end result of most renal and some systemic diseases, is a common condition where renal function is compromised due to fibrosis. During renal fibrosis, calreticulin, a multifunctional chaperone of the endoplasmic reticulum (ER) is up‐regulated in tubular epithelial cells (TECs) both in vitro and in vivo. Proteomic analysis of cultured TECs overexpressing calreticulin led to the identification of the family of 14‐3‐3 proteins as key proteins overexpressed as well. Furthermore, an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…14‐3‐3 proteins belong to the family members of acidic intracellular proteins (Stevers et al, 2018). It was reported that 14‐3‐3 proteins could regulate the process of cell apoptosis (Rizou et al, 2018). For example, 14‐3‐3‐η could suppress apoptosis caused by ischemia and diabetes (Chen et al, 2007; Gurusamy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…14‐3‐3 proteins belong to the family members of acidic intracellular proteins (Stevers et al, 2018). It was reported that 14‐3‐3 proteins could regulate the process of cell apoptosis (Rizou et al, 2018). For example, 14‐3‐3‐η could suppress apoptosis caused by ischemia and diabetes (Chen et al, 2007; Gurusamy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Stratifin (SFN) is a cell cycle checkpoint protein and a regulator of mitotic translation. To response the DNA damage, SFN often plays a role in inhibiting DNA errors during mitosis [4,5]. Generally, SFN is expressed at low levels on the nervous and reproductive systems, including in the cortex, retina, placenta, and ovary [6].…”
Section: Introductionmentioning
confidence: 99%
“…Stratifin (SFN) is a member of the 14-3-3 protein family, a highly preserved group of proteins participating by 7 isoforms. SFN is engaged with many significant biological functions like cell cycle apoptosis, regulation of signal transduction pathways, and cell proliferation [ 24 , 25 ].. SFN often plays a role in inhibiting DNA errors during mitosis to respond to DNA damage [ 26 ]. SFN had a high expression of malignant progression in early-stage lung adenocarcinoma [ 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%